Notes: (5) An Encrusted Urn from Aberlemno, Angus - Childe, V Gordon (Proceedings of the Society of Antiquaries of Scotland, 1943)
The capstone of a small cist was discovered during ploughing. The vessel within was protected by a cist of slabs, built apparently after the urn was set in place rather in the manner of a house of cards. The substructure of the cist was an irregular pentagon formed of five principal slabs. The urn contained the burnt bones of an adolescent.